The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10801-010-0234-8
|View full text |Cite
|
Sign up to set email alerts
|

Sharply transitive sets in quasigroup actions

Abstract: This paper forms part of the general development of the theory of quasigroup permutation representations. Here, the concept of sharp transitivity is extended from group actions to quasigroup actions. Examples of nontrivial sharply transitive sets of quasigroup actions are constructed. A general theorem shows that uniformity of the action is necessary for the existence of a sharply transitive set. The concept of sharp transitivity is related to two pairwise compatibility relations and to maximal cliques within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…For instance, Jonathan Smith has intensively studied quasigroup and loop representations in a series of papers [9][10][11]. Also, the study of sharply transitive sets in quasigroup actions can be found in [7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Jonathan Smith has intensively studied quasigroup and loop representations in a series of papers [9][10][11]. Also, the study of sharply transitive sets in quasigroup actions can be found in [7].…”
Section: Introductionmentioning
confidence: 99%
“…We consider a quasigroup obtained by permuting entries in the multiplication table of the direct product S 3 × Z 2 of the symmetric group S 3 with the 2-element additive group Z 2 of integers modulo 2 as in [3], and want to establish a non-regular approximate symmetry from a quasigroup homogeneous space of degree 4 in this paper.…”
Section: Preliminaries and Introductionmentioning
confidence: 99%
“…Six elements of S 3 are denoted as three rotations ρ 0 = (0), ρ 1 = (021), ρ 2 = (012), and three reflections σ 0 = (12), σ 1 = (02), σ 2 = (01). Z 2 = {0, 1} as in [3]. Consider a relation λ · µ = ν in S 3 .…”
Section: Preliminaries and Introductionmentioning
confidence: 99%
See 1 more Smart Citation